(untitled) (Scientia Agricola, 1994)
The use of a new soil particle size distribution analysis methodology is presented in connection with the study of particle size distribution in soils covered by natural forest and sugar cane crop cultivated during 16, 30 and 50 years, continuously. The technique is based on the attenuation of a gamma-ray beam by a conventional soil/water suspension under sedimentation. Results show a significant difference in clay content for the upper soil layer as a function of sugar cane cultivation.